Pandemic H1N1 influenza-associated myocarditis in a patient with Castleman's disease. Issue 1 (February 2013) - Roca, B; Penades, M; Resino, E
We report on a patient with longstanding multicentric Castleman's disease, hyaline-vascular type, who presented with nearly-fatal myocarditis associated with a 2009 pandemic H1N1 influenza virus infection. This is the first case of such an association described in the literature.